High serum levels of the C-propetide of type V collagen (PRO-C5) are prognostic for short overall survival in patients with pancreatic ductal adenocarcinoma - Nissen, Neel I.; Johansen, Astrid Z.; Chen, Inna M.; Jensen, Christina; Madsen, Emilie A.; Hansen, Carsten P.; Thorlacius-Ussing, Jeppe; Karsdal, Morten; Johansen, Julia S.; Diab, Hadi M. H.; Jørgensen, Lars N.; Willumsen, Nicholas (Frontiers in Molecular Biosciences, 2023)
Introduction: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a pronounced fibrotic tumor microenvironment, which impairs treatment response. Type I and V collagens are responsible for the densely packed fibrils in the tumor fibrosis environment. While the role of the major type I collagen in cancer is well described, less is known about the minor type V collagen. Quantifying collagen propeptides in serum has been shown to have prognostic and predictive value. In this study, we evaluated the clinical utility of measuring the propeptide of type V collagen (PRO-C5) in serum from a discovery cohort and a validation cohort of patients with PDAC as well as in non-pancreatic solid tumor types to explore the relevance of the PRO-C5 biomarker in cancer. Methods: Serum PRO-C5 was measured in three cohorts: a discovery cohort (19 healthy controls, 12 patients with chronic pancreatitis and 33 patients with PDAC (stage I-IV)), a validation cohort (800 patients with PDAC (stage I-IV)), and a non-pancreatic solid tumor type cohort of 33 healthy controls and 200 patients with 10 different non-pancreatic solid tumor types. The levels of serum PRO-C5 in patients with cancer were compared to levels in healthy controls. The association between PRO-C5 levels and overall survival (OS) was evaluated in patients with PDAC after adjusting for established prognostic factors. Results: PRO-C5 was significantly increased in serum from patients with PDAC compared to healthy controls (p < 0.001). High PRO-C5 levels were significantly associated with short OS in both the discovery- and the validation cohort, especially in early stages of PDAC (validation cohort stage II, HR = 2.0, 95%CI1.2-3.4). The association was independent of other prognostic parameters including stage, performance status and CA19-9. Furthermore, serum levels of PRO-C5 were significantly increased in serum from patients with other non-pancreatic solid tumor types compared to healthy controls. Conclusion: High levels of serum PRO-C5 is prognostic for short OS in patients with PDAC and may provide clinical value in many other tumor types beyond PDAC. This underlines the importance of type V collagen in tumor fibrosis. PRO-C5 could have the potential to be used in several aspects within drug discovery, patient stratification and drug efficacy.